Broadband regulation and government investment in nationwide ultra fast fribre broadband networks: Evidence from New Zealand - Bronwyn Howell (International Telecommunications Society (ITS), 2013)
New Zealand stands apart from its OECD counterparts as one of the few countries pursuing government investment in a nationwide fibre network. As in the past, when it stood apart with its 'light-handed' regulatory approach, New Zealand's experience can inform other jurisdictions. This paper contributes by documenting and analysing the chronological history of the key political, regulatory and industry actions taken to implement the government fibre investment policy, between 2008 and September 2013. The chronology reveals an industry currently in considerable disarray. A critical political economy and industrial organisation-based analysis proposes that the incremental and pathdependent nature of the evolution of New Zealand's industry-specific regulatory environment resulted in a set of arrangements ill-suited to oversee the transition from a copper-based to a fibrebased fixed line access infrastructure. It contends that the current disarray was an inevitable outcome of a lack of co-ordinated oversight of sector policy and governance that allowed the fibre network investment to proceed without clearly-articulated overarching and forward-looking competition and regulation policies integrating legacy regulations and investments into the fundamentally different environment created by the government's revolutionary fibre policy. The result was the fragmentation of regulatory responsibility across many parties on the basis of network technology type. Consequently, each pursued its own objectives in isolation from the others, which led to a crisis in December 2012 when a regulatory decision about copper prices threatened the viability of the fibre project. Absence of clear and co-ordinated leadership of sector strategy in response to the crisis has resulted in the government's integrity being undermined and a loss of confidence amongst private sector investors.
Keywords: 330